Penggunaan Media Audio Visual untuk Meningkatkan Keterampilan Menulis Siswa Kelas VI SD - Nur Najmi Lailah; Ibnu Muthi (Jurnal Pendidikan Dirgantara, 2025)
This study aims to explore how effective audio-visual media can improve grade 6 students’ ability to recognize punctuation in poetry. Literacy skills, especially in writing and understanding punctuation in poetry, are a big challenge for primary school students around the world. Lack of understanding of the structural elements of poetry and the role of punctuation often result in difficulties for student to convery their meaning and feelings correctly thorugh writing. The approach taken in this research was a literature study that examined various scholarly sources related to literacy, poetry teaching, and the use of audio-visual media. The results of the analiysis show that audio-visual media can signicantly improve students’ motivation, comprehension and writing sklills. This media promotes a more interactive and relevant learning experience, so that students can understand the application not only from a technical perspective, but also as an aesthetic element that strengthens the meaning and expression in poetry. From these finfings, it is recommended to integrate audio-visual media in teching poetry as an innovative step to overcome liteacy problems and improve the quality of indonesian language education at the primary level.